Predicting maintenance of attendance at walking groups: testing constructs from three leading maintenance theories - Kassavou, Aikaterini; Turner, Andrew; Hamborg, Thomas; French, David P (Health psychology, 2014)
Little is known about the processes and factors that account for maintenance, with several theories existing that have not been subject to many empirical tests. The aim of this study was to test how well theoretical constructs derived from the Health Action Process Approach, Rothman's theory of maintenance, and Verplanken's approach to habitual behavior predicted maintenance of attendance at walking groups. 114 participants, who had already attended walking groups in the community for at least 3 months, completed a questionnaire assessing theoretical constructs regarding maintenance. An objective assessment of attendance over the subsequent 3 months was gained. Multilevel modeling was used to predict maintenance, controlling for clustering within walking groups. Recovery self-efficacy predicted maintenance, even after accounting for clustering. Satisfaction with social outcomes, satisfaction with health outcomes, and overall satisfaction predicted maintenance, but only satisfaction with health outcomes significantly predicted maintenance after accounting for clustering. Self-reported habitual behavior did not predict maintenance despite mean previous attendance being 20.7 months. Recovery self-efficacy, and satisfaction with health outcomes of walking group attendance appeared to be important for objectively measured maintenance, whereas self-reported habit appeared not to be important for maintenance at walking groups. The findings suggest that there is a need for intervention studies to boost recovery self-efficacy and satisfaction with outcomes of walking group attendance, to assess impact on maintenance.